2013
DOI: 10.3109/21678421.2013.852590
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis: Analysis of ALS cases in a predominantly admixed population of Ecuador

Abstract: Recent studies suggest amyotrophic lateral sclerosis (ALS) prevalence, incidence, and age of onset are heterogeneous across populations. These include studies from South America (SA) where lower prevalence, earlier onset, and reduced survival time of ALS are reported. However, the scarcity of epidemiological and clinical data confounds effective comparison. To investigate ALS incidence in the predominantly admixed population of Ecuador, we analyzed patient data. We analyzed case data from two major hospitals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…A recent review of the ethnic variation of incidence in ALS showed lower rates in Africans, Asians, and Hispanics compared to Whites(12). Moreover, in a study of the Cuban population, the overall mortality rate was similar to the United States Hispanic mortality rate and even lower in Blacks and mixed race individuals(13) and an Ecuadorian study showed a reduced incidence of ALS in this South American population compared to the United States(14). However another study of an inner city population in London showed a similar incidence of ALS in patients with a European ancestry compared to an African ancestry suggesting similar incidence rates in these groups, although the confidence intervals are large(15).…”
Section: Discussionmentioning
confidence: 77%
“…A recent review of the ethnic variation of incidence in ALS showed lower rates in Africans, Asians, and Hispanics compared to Whites(12). Moreover, in a study of the Cuban population, the overall mortality rate was similar to the United States Hispanic mortality rate and even lower in Blacks and mixed race individuals(13) and an Ecuadorian study showed a reduced incidence of ALS in this South American population compared to the United States(14). However another study of an inner city population in London showed a similar incidence of ALS in patients with a European ancestry compared to an African ancestry suggesting similar incidence rates in these groups, although the confidence intervals are large(15).…”
Section: Discussionmentioning
confidence: 77%
“…), treatment (Dubrovsky & Sica ), epidemiology (Dubrovsky & Sica , Bucheli et al . ) and economic cost (Bucheli et al . ) of ALS in South America, but only one Chinese study referred to caregivers’ burden (Cui et al .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of ALS in the world varies from 0.4 per 100,000 per year (Ecuador) [8] to 3.83 per 100,000 per year [9] (Scotland), and the prevalence ranges from 0.1 (Somalia)…”
Section: Resultsmentioning
confidence: 99%